Experimental study on thermal performance of a water/steam cavity receiver with solar simulator. (December 2017) - Wan, Zhenjie; Qaisrani, Mumtaz A.; Du, Xuancheng; Wei, Jinjia; Fang, Jiabin; Zhang, Jian
Abstract: The performance of cavity receiver plays a fatal role in light-heat conversion process in a concentrating solar power (CSP) plant. In our present work, an experimental platform is designed and built, in which a solar simulator consisting of seven mutually independent xenon lamp units is used for supplying the solar energy needed. The cold start-up and steady state performance of the cavity receiver were studied under 0.5MPa. The results show that for a certain cavity structure, temperatures on boiling panels and thus the heat loss can be affected not merely by the heat flux, other parameters can influence the temperature of absorbing surfaces, such as the heat transfer in the boiling tubes, fluid flow states and the wind effect, so the temperature distribution is highly non-uniform on boiling panels. However, the temperatures of passive surfaces depend greatly on the input solar energy, thus the heat losses of the passive surfaces will vary with the input energy. Overheat occurs if a high heat flux doesn't have a sufficient heat transfer inside boiling tubes internal. The stagnation zone does exist in the cavity and its boundary varies with a different input energy, thus the convective heat loss can be affected. The cavity receiver thermal efficiency is 72.92% under 0.5MPa, may be the reason behind this low efficiency is the strong cooling wind of the solar simulator.